2014
DOI: 10.1051/0004-6361/201424143
|View full text |Cite
|
Sign up to set email alerts
|

A resolved, au-scale gas disk around the B[e] star HD 50138

Abstract: HD 50138 is a B[e] star surrounded by a large amount of circumstellar gas and dust. Its spectrum shows characteristics which may indicate either a pre-or a post-main-sequence system. Mapping the kinematics of the gas in the inner few au of the system contributes to a better understanding of its physical nature. We present the first high spatial and spectral resolution interferometric observations of the Brγ line of HD 50138, obtained with VLTI/AMBER. The line emission originates in a region more compact (up to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 84 publications
6
46
1
Order By: Relevance
“…It was included in the sample as a possible protoplanetary disk and is often treated as such in the literature, but see e.g. Ellerbroek et al (2015) for a discussion of its unclear nature. Its CO 6−5 upper limit falls between our R c = 10 and 50 au models, while the [C ] detection is an order of magnitude brighter than any of our Herbig Ae/Be disk models.…”
Section: Herbig Ae/be Systems (Spectral Types B a F)mentioning
confidence: 99%
“…It was included in the sample as a possible protoplanetary disk and is often treated as such in the literature, but see e.g. Ellerbroek et al (2015) for a discussion of its unclear nature. Its CO 6−5 upper limit falls between our R c = 10 and 50 au models, while the [C ] detection is an order of magnitude brighter than any of our Herbig Ae/Be disk models.…”
Section: Herbig Ae/be Systems (Spectral Types B a F)mentioning
confidence: 99%
“…The star has a measured rotational speed 90 km s −1 , and is inferred to have a disk inclined at 56 Borges Fernandes et al 2011. Using the spectrointerferometric technique, Ellerbroek et al (2015) resolved its au-scale disk with a measured photocenter offset, possibly caused by an asymmetric structure of the disk or a binary companion. These authors favored a post-main sequence status for HD 50138, because of the presence of high transition lines, such as Paschen, Bracket and Pfund series less commonly observed in PMS stars, and because the star is apparently not associated with an SFR, supported by our assessment.…”
Section: Census Of Neighboring Regionsmentioning
confidence: 99%
“…4 we present an elaborative census of each target in order to rule out the possibility of stellar youth for eight B[e] stars, adding support to their evolved status. Cidale et al (2001); (c) Sheikina et al (2000); (d) Voroshilov et al (1985); (e) Friedemann (1992); ( f ) Ellerbroek et al (2015); (g) Miroshnichenko et al (2003); (h) Miroshnichenko et al (2001); (i) Caratti o Garatti et al (2015); ( j) Malfait et al (1998); (k) Malkov et al (2006); (l) Dyck & Milkey (1972); (m) Zickgraf (2001). Zhang et al (2005), and that of Herbig stars is from de Winter et al (2001).…”
Section: Introductionmentioning
confidence: 98%
“…Visual-wavelength interferometry, for instance with the CHARA/VEGA instrument, can provide now fundamentally new constraints to distinguish between these models. So far, Hα spectrointerferometry have been reported for only two HAeBe stars, namely AB Aurigae (Rousselet-Perraut et al 2010) and MWC158 (Ellerbroek et al 2014). In both cases, the measurements indicate that the line-emitting region is more extended than what would be expected from a magnetosphere accretion scenario and the measurements appear more consistent with an X-wind or disk-wind geometry, although it should be noted that the measurement uncertainties are still very large in the current data sets.…”
Section: Gas Kinematics Constraintsmentioning
confidence: 65%
“…Such gas kinematics studies can be conducted using AMBER's unique high spectral dispersion mode of R = λ/∆λ = 12 000. For the Herbig B[e] stars V921 Scorpii (Kraus et al 2012a) and MWC158 (Ellerbroek et al 2014), it was found that the Brγ-emitting gas is in Keplerian rotation in the inner disk. Observations on MWC297, on the other hand, had to invoked a more complex disk wind model (Weigelt et al 2011).…”
Section: Gas Kinematics Constraintsmentioning
confidence: 99%